Security and Privacy for Mobile Edge Caching: Challenges and Solutions - Ni, Jianbing; Zhang, Kuan; Vasilakos, Athanasios V. (IEEE wireless communications, 2021)
Mobile edge caching is a promising technology for next-generation mobile networks to effectively offer service environments and cloud-storage capabilities at the edge of networks. By exploiting the storage and computing resources at the network edge, mobile edge caching can significantly reduce service latency, decrease network load, and improve the user experience. On the other hand, edge caching is subject to a number of threats regarding privacy violations and security breaches. In this article, we first introduce the architecture of mobile edge caching, and address the key problems regarding why, where, what, and how to cache. Then we examine the potential cyber threats, including cache poisoning attacks, cache pollution attacks, cache side-channel attacks, and cache deception attacks, which result in huge concerns about privacy, security, and trust in content placement, content delivery, and content usage for mobile users, respectively. After that, we propose a service-oriented and location-based efficient key distribution protocol (SOLEK) as an example in response to efficient and secure content delivery in mobile edge caching. Finally, we discuss the potential techniques for privacy-preserving content placement, efficient and secure content delivery, and trustful content usage, which are expected to draw more attention and efforts into secure edge caching.